2023
DOI: 10.1002/star.202200217
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inulin on Thermal Properties, Pasting, Rheology, and In Vitro Digestion of Potato Starch

Abstract: In this study, different concentrations of natural inulin (IN) are compounded with potato starch (PoS) to prepare an inulin‐potato starch (PoS‐IN) compound system, and the physical and chemical properties of the compound system such as pasting, rheology, and digestion are investigated. According to the findings, the complex system's viscosity, breakdown, and setback are greatly reduced. The addition of IN also prevents the complex system from being pasted and increases the stability of the PoS. The gel structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…While previous studies have indicated that water deficit leads to an increase in RDS and SDS content, and a decrease in RS content, this study found that RS content increased under water deficit [ 50 52 ]. This could be due to several factors, including a decrease in the synthesis of B-type crystallinity and an increase in A-type crystallinity [ 53 , 54 ], which is less susceptible to be attacked by α-amylase or glucoamylase [ 55 ]. Additionally, water deficit can lead to a reduction in starch particle size, which is directly proportional to digestibility.…”
Section: Resultsmentioning
confidence: 99%
“…While previous studies have indicated that water deficit leads to an increase in RDS and SDS content, and a decrease in RS content, this study found that RS content increased under water deficit [ 50 52 ]. This could be due to several factors, including a decrease in the synthesis of B-type crystallinity and an increase in A-type crystallinity [ 53 , 54 ], which is less susceptible to be attacked by α-amylase or glucoamylase [ 55 ]. Additionally, water deficit can lead to a reduction in starch particle size, which is directly proportional to digestibility.…”
Section: Resultsmentioning
confidence: 99%
“…The protein contents of PSPS and PSPRS were lower than 1%, indicating that the purities of PSPS and PSPRS were relatively high [33]. The protein and starch contents of PSPRS showed a significant difference from PSPS (p < 0.05), indicating the destruction of structure upon enzymatic hydrolysis [34]. Compared with PSPS, the amylose content of PSPRS was significantly improved (p < 0.05).…”
Section: Physicochemical Propertiesmentioning
confidence: 94%
“…The in vitro digestion of the sample was performed with slight modifications based on the method described by our group [24]. A total of 4 mL of 0.1 mol/L sodium acetate buffer solution was added to the weighed sample (200 mg, dry basis).…”
Section: In Vitro Digestionmentioning
confidence: 99%